2003
DOI: 10.1177/03635465030310063101
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Arthroscopic Medial Meniscal Repair Technique

Abstract: Repairs of the longitudinal posterior horn of the medial meniscus during an anterior cruciate ligament reconstruction with nonweightbearing for 5 weeks can be performed with an equivalent high degree of clinical success for both repair techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 35 publications
0
58
0
1
Order By: Relevance
“…Our findings reveal that the differences between CPM treated and immobilized meniscal cells can be as early as 24 h. In these experiments we have compared the effects of CPM with those of immobilization because the experimental conditions for both immobilization and CPM can be controlled precisely. Additionally, mobilization and immobilization are two frequently used modalities for the treatment of meniscal pathologies [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings reveal that the differences between CPM treated and immobilized meniscal cells can be as early as 24 h. In these experiments we have compared the effects of CPM with those of immobilization because the experimental conditions for both immobilization and CPM can be controlled precisely. Additionally, mobilization and immobilization are two frequently used modalities for the treatment of meniscal pathologies [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one clinical manuscripts were identified that studied the following all-inside meniscus repair devices: the meniscus arrow, 1,2,13,16,19,20,24,25,27,29,33,35,36,38 T-Fix (Acufex Microsurgical, Inc, Mansfield, MA) 4,9,10,14,21,38 and FasT-Fix (Smith & Nephew Endoscopy, Boston, MA) 17,23 devices, the meniscus screw, 11,15,18,37 the Biostinger (Linvatec, Largo, FL), 6,8 the RapidLoc (DePuy Mitek, Norwood, MA) device, 18,31 a meniscal repair system 26 and a meniscal stapler. 28 The most studied device was the meniscus arrow with 14 studies looking at clinical outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Only two prospective randomized studies, 1,18 two prospective comparative studies, 8,35 and three retrospective comparative studies 19,36,38 were found relating to all-inside meniscal repair devices. The lack of randomized controlled studies does not allow us to make any definitive suggestions on the use of various all-inside meniscal repair devices.…”
mentioning
confidence: 99%
“…However, preservation of meniscal tissue is an over whelming rationale in young active patients and several authors have demonstrated that tears located in the central onethird avascular zone can be successfully repaired. 6,12,58,59,68,80,82,90 sults of meniscal repair using fixators, such as arrows, 22,29,43,48,50,83,84 staples, 49 and all-inside biodegradable screws 32,38,69 ; however, arthroscopicassisted suture repair remains the gold standard and is our preferred method. In addition, we have demonstrated that a rehabilitation program that implements immediate knee motion the first postoperative day after meniscus repair (performed either alone or with anterior cruciate ligament [ACL] reconstruction) is not deleterious to the healing meniscus tissue and prevents knee arthrofibrosis.…”
mentioning
confidence: 99%